Peningkatan Gizi Ibu Hamil Melalui Edukasi Mengenai Pemenuhan Nutrisi Pada Kelas Ibu Hamil Di Desa Jangur Kabupaten Probolinggo - Wahyudi, Kalvin Edo; Abdullah, Azriel Delmiro Frizzy; Sari, Cindy Kartika; Mustikasari, Indracahyaning; Nurhidayah, Rachmadita; Faj’jrina, Faradila Sofia Nur (Universitas Gajah Putih, Indonesia, 2023)
Stunting is a problem of chronic malnutrition due to the provision of food that is not in accordance with the nutritional needs of toddlers. Stunting can occur when fetus is still in the womb and will only be seen after children start turning two years old. Stunting prevention is carried out during the first 1000 days of a child's life. Therefore, counseling on stunting prevention is necessary for pregnant women. The community service activity carried out by the MBKM Thematic KKN Students Group 55 of the East Java